2014
DOI: 10.4172/2155-9546.1000230
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of Arabinoxylan-Oligosaccharides, Oligofructose and their Monomeric Sugars by Hindgut Bacteria from Siberian Sturgeon and African Catfish in Batch Culture in vitro

Abstract: The in vitro fermentation of two Non-Digestible Oligosaccharide (NDO) preparations, ArabinoxylanOligosaccharides (AXOS) and Oligofructose (OF), and their respective monomeric sugars, xylose and fructose, were investigated by hindgut microbiota of two major aquaculture fish species, Siberian sturgeon (Acipenser baerii) and African catfish (Clarias gariepinus). Inocula from the hindgut of both fish species were incubated for 48 h in bottles containing 1.0% of one of four substrates, i.e. AXOS, OF, xylose or fruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…These studies have demonstrated that prebiotics (i.e., L-sorbose, xylitol, and resistant starch) can selectively stimulate the growth of butyrate producers and increase the production of butyric acid in batch cultures. Accordingly, several substrates, such as arabinoxylan, whole wheat, soybean oligosaccharides, isomaltooligosaccharides, raffinose, gentiobiose, lactosucrose, arabinoxylanoligosaccharides, oligofructose, xylose, and fructose, have been shown to enhance the levels of SCFAs in batch cultures with gut microbes of common carp (Cyprinus carpio) (Kihara and Sakata, 2002), Nile tilapia (Oreochromis niloticus), and European seabass (Dicentrarchus labrax) (Leenhouwers et al, 2008), Siberian sturgeon (Acipenser baerii), and African catfish (Clarias gariepinus) (Geraylou et al, 2014). In this study, mud crab (Scylla paramamosain) was used as a model to investigate the effects of two kinds of carbohydrate (galactooligosaccharides [GOS] and resistant starch [RS]) on gut microbiota and SCFA production using in vitro anaerobic fermentation cultures.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have demonstrated that prebiotics (i.e., L-sorbose, xylitol, and resistant starch) can selectively stimulate the growth of butyrate producers and increase the production of butyric acid in batch cultures. Accordingly, several substrates, such as arabinoxylan, whole wheat, soybean oligosaccharides, isomaltooligosaccharides, raffinose, gentiobiose, lactosucrose, arabinoxylanoligosaccharides, oligofructose, xylose, and fructose, have been shown to enhance the levels of SCFAs in batch cultures with gut microbes of common carp (Cyprinus carpio) (Kihara and Sakata, 2002), Nile tilapia (Oreochromis niloticus), and European seabass (Dicentrarchus labrax) (Leenhouwers et al, 2008), Siberian sturgeon (Acipenser baerii), and African catfish (Clarias gariepinus) (Geraylou et al, 2014). In this study, mud crab (Scylla paramamosain) was used as a model to investigate the effects of two kinds of carbohydrate (galactooligosaccharides [GOS] and resistant starch [RS]) on gut microbiota and SCFA production using in vitro anaerobic fermentation cultures.…”
Section: Introductionmentioning
confidence: 99%
“…) and Siberian sturgeon and African catfish (Geraylou et al . ). Additionally, organic acids and their salts, including sodium butyrate, acetate, propionate, formate or citrate, have been shown to decrease the gut SCFAs in red hybrid tilapia ( Oreochromis sp.)…”
Section: Factors Influencing the Formation Of Scfasmentioning
confidence: 97%
“…Although many studies have reported good results on the effects of prebiotic supplementation on the production of SCFAs in the gut of aquatic animals, in vitro fermentation has been used as a simpler approach. In vitro cultures of arabinoxylan, whole wheat, soybean-oligosaccharides, isomalto-oligosaccharides, raffinose, gentiobiose, lactosucrose, AXOS, oligofructose, xylose or fructose using inocula of fish gut microbes have yielded high production of major SCFAs in fish species such as common carp (Cyprinus carpio) (Kihara & Sakata 2002), Nile tilapia (Oreochromis niloticus) and European seabass (Dicentrarchus labrax) (Leenhouwers et al 2008) and Siberian sturgeon and African catfish (Geraylou et al 2014). Additionally, organic acids and their salts, including sodium butyrate, acetate, propionate, formate or citrate, have been shown to decrease the gut SCFAs in red hybrid tilapia (Oreochromis sp.)…”
Section: Factors Influencing the Formation Of Scfasmentioning
confidence: 99%
“…Although SCFAs are thought to be mainly produced through carbohydrate fermentation by microorganisms, all three feeds had detectable SCFAs in this study (Table 2). Secondly, the amounts and species of SCFAs are significantly influenced by carbohydrate substrates (Hao et al, 2017a;Mountfort et al, 1993;Kihara and Sakata, 1997;Probert et al, 2004;Geraylou et al, 2014). Starch is seemingly more easily utilized to produce SCFAs through fermentation by gut microbiota in many fish (Kihara and Sakata, 1997; Van, 1994;Leenhouwers et al, 2007).…”
Section: Effects Of Diet On Hindgut Scfa Accumulation and The Growth Of Grass Carpmentioning
confidence: 99%